EFEKTIVITAS METODE EDUKASI BERBASIS MOBILE EDU APP SEBAGAI UPAYA INTERVENSI PENURUNAN STUNTING DENGAN PENDEKATAN ASUH, ASIH, ASAH - Sylvia Anjani; Fitria Dewi Puspita Anggraini; Vilda Ana Veria Setyawati; Aprianti Aprianti; Agustina Nur Indriati (Universitas Labuhanbatu, 2022)
Stunting is a national health development program that involves specific and sensitive interventions in it. Prevention of stunting has been carried out since 2018 starting from 100 priority areas. Unfortunately, the city of Semarang is not yet included in this area. Some people still cannot understand the problem of stunting properly. The purpose of this study to measure the effectiveness of using Android-based educational mobile media apps with a nurturing, compassionate, and honing approach to posyandu cadres. This study is an analytic observational study with a pre-post test design. The number of questions in the questionnaire is 15 items related to the level of stunting knowledge. The intervention was carried out to 20 posyandu cadres to measure the level of knowledge based on the average difference in the results of the pre-post test using the Wilcoxon difference test. The effectiveness of the educational method using the application is measured by the Gain Score formula. Statistical results obtained a p-value of 0.001, meaning that there is a significant difference in the level of knowledge of cadres after education using a mobile education app with a gain-score of 0.48, so it can be said that the educational activities carried out have moderate effectiveness in increasing the knowledge of cadres in Tanjung Mas village.